Effect of Mg2+ and Fe2+ Concentrations in Culture Medium on CGF Formation from Microalgae Chlorella Pyrenoidosa Ink and Analysis of Amino Acids by Liquid Chromatography-Mass Spectrometry - Kusmiati,; Rahmawati, Witry; Agustini, Ni Wayan Sri (UI Scholars Hub, 2015)
Chlorella pyrenoidosa (C. pyrenoidosa) contains Chlorella Growth Factor (CGF), which consists of proteins and polysaccharides. CGF is located inside the nucleus of cells and is beneficial to humans as a food supplement, an immunity booster, and an antioxidant. CGF formation of C. pyrenoidosa is influenced by medium composition. C. pyrenoidosa INK was cultured in a modified basal medium (MBM) with various concentrations of Mg2+ (0.5, 1.0, and 1.5 g/L) and Fe2+ (3.5×10-4 and 5.0×10-4 g/L). The experiments were performed and analyzed under a completely randomized design using a 2-L bottle with three replications. The results showed that MBM with 1.0 g/L of Mg2+ and 3.5×10-4 g/L of Fe2+ yielded the optimal growth curve for C. pyrenoidosa. Analysis of protein content was carried out using the Lowry method with a spectrophotometer at λ=750 nm, and the obtained results were 0.0974 mg/mL (extract) and 6.4097 mg/ml (supernatant). Furthermore, analysis of glucose content was carried out using the phenol sulfate method (λ = 490 nm), and the obtained results were 49.331 ppm (extract) and 1566.911 ppm (supernatant). Analysis of amino acids in CGF using liquid chromatography-mass spectrometry (LC-MS) indicated the presence of tyrosine, proline, glutamate, alanine, valine, tryptopan, phenylalanine, methionine, and leucine-isoleucine.